Modeling Human Behavior in Human-Robot Interactions - Zgonnikov, Arkady; Thill, Serge; Beckerle, Philipp; Jonker, Catholijn M. (ACM/IEEE International Conference on Human-Robot Interaction, 2022)
This interdisciplinary workshop aims to break boundaries between the researchers who develop human models (e.g., from the fields of human factors, cognitive psychology, and computational neuroscience) and roboticists who use human models in different human-robot interaction (HRI) contexts. The keynote talks, contributed submissions, and interactive discussions will focus on the questions such as: How can modeling humans help us understand and design human-robot interactions? What kinds of models are useful for which HRI contexts (physical/cognitive interactions) and purposes (behavior prediction/personalization/theory -of- mind/etc.)? What common lessons can be learned from human behavior modeling in HRI across different application domains? How can modeling humans in HRI tasks help us to better understand human cognition/behavior? By stimulating an interdisciplinary conver-sation around these questions, we aim to raise awareness of the benefits of modeling and expose the wider HRI community to a variety of different modeling approaches, and facilitate the HRI researchers who already engage in modeling to exchange views on methodology of modeling and best nractices from diverse fields.
CRIS-Team Scopus Importer:2022-11-04
Keywords: human behavior; Human-robot interaction; modeling